FAKTOR FAKTOR YANG MEMPENGARUHI MINAT KUNJUNGAN ULANG KE DAYA TARIK OBJEK SIWANG PARADISE KOTA AMBON - Yosevita. Th Latupapua (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
Siwang paradise is a natural tourist attraction that has a fantastic number of visits, but the visit underwent a very significant change. The purpose of this study was to analyze the factors that influence the interest in revisiting the Siwang Paradise natural tourist attraction. The method used is linear regression analysis method, the sampling technique is accidental sampling (direct samples based on conditions in the field), namely the sampling technique shown directly to tourists when research is carried out at the Siwang Paradise tourist attraction. Meanwhile, to obtain additional information that can support the accuracy of the research data, the researchers used respondents related to the research being carried out, the respondents were divided into two groups, namely: 1) Visitors, who were encountered while conducting research; 2) the manager or more clearly is the owner of the object. The collected data were analyzed using descriptive analysis and multiple regression analysis. This model is used in this study, because it wants to get information on factors of attraction, facilities, accessibility and services on the interest of repeat visits to the Siwang Paradie object simultaneously and partially. In multiple linear regression analysis, to ascertain whether the estimated model equation is unbiased, the classical assumption test will be carried out which includes normality test, multicollinearity test and heteroscedasticity. The results showed that the variable that had a significant effect on the interest in revisiting the Siwang paradise object was tourism services, with a significance value of (0.002), t-count is 3.366, which means that t-count is greater than t-table, .